THE EFFECT OF NUMBER HEAD TOGETHER (NHT) TECHNIQUE ON STUDENTS’ READING COMPREHENSION AT TENTH YEAR OF SMA N 1 BUKITTINGGI - Mega Gusna Yenti; Rusdi Thaib; Aryuliva Adnan (Universitas Negeri Padang, 2016)
This research aims to see whether students who were taught by using Number Together technique had better reading comprehension than those who were taught by using technique used by English teachers in teaching reading which was called in this technique as conventional technique. The sample of this research was X IPA 3 as the experimental group which consists of 35 students and X IPA 5 as the control group which consists of 35 students. The data of this research was reading test (posttest) scores which were analyzed by using t-test. It was found that there was significantly difference on student’ reading comprehension of tenth year students who were taught by using Number Head Technique. The reasult showed that tcount was 8.73 and ttable was 2.00 in the level of significant 0.05 which means tcount was bigger than ttable. Finally, it could be concluded that the students who were taught by using Number Head Together technique had better reading comprehension thann those who were taught by using conventional technique.